Genetic divergence, path coefficient and cluster analysis of chickpea (Cicer arietinum) cultivars, in the mid-altitudes of Meghalaya - PANDEY, AVINASH; GUPTA, SANJAY; KUMAR, AMIT; THONGBAM, P D; PATTANAYAK, A (The Indian Journal of Agricultural Sciences, 2026)
Twenty two chickpea (Cicer arietinum L.) genotypes were evaluated during rabi seasons of 2007-08 and 2008-09 to explore the possibility of introducing chickpea crop into the cropping system of the mid-altitudes of Meghalaya. Luxuriant chickpea growth with a wide spectrum of variability for plant height, number of branches/plant, days to flowering, number of pods/plant and 100 seed weight was observed. The genotypic variance was moderate to high for the said characters which resulted in moderate to high heritability and genetic advance values. Grain yield/plant was positively and significantly correlated with days to flowering, plant height, number of branches/plant, number of pods/plant and 100 seed weight. Moderate to high heritability and genetic advance of these plant characters vis-a-vis their positive association and direct positive effect on grain yield/plant suggested for their consideration during selection of high yielding genotypes. All the test chickpea genotypes could be grouped into five distinct clusters. An analysis of the percentage contribution of individual characters towards genetic diversity revealed that days to flowering, 100-seed weight and number of pods/plant were the major characters contributing to genetic diversity in chickpea. Based on the results it may be concluded that chickpea can be successfully grown in Meghalaya and chickpea improvement can be undertaken in the mid hill conditions of north eastern hill region of India.